2021
DOI: 10.1371/journal.pone.0254792
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the parental reflective functioning questionnaire and association with maternal postpartum depression and comorbid symptoms of psychopathology

Abstract: Parental reflective functioning (PRF) refers to the parent’s capacity to envision mental states in the infant and in themselves as a parent, and to link such underlying mental process with behavior, which is important for parenting sensitivity and child socio-emotional development. Current findings have linked maternal postpartum depression to impaired reflective skills, imposing a risk on the developing mother–infant relationship, but findings are mixed, and studies have generally used extensive methods for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 107 publications
(150 reference statements)
9
29
1
Order By: Relevance
“…In contrast, internal consistencies tend to be higher in studies that administered the PRFQ to samples in which parents were primarily college educated, partnered, and not recruited based on being at-risk (e.g., Carlone & Milan, 2021; Moreira & Fonseca, 2022; Nijssens et al, 2020)—though see Pazzagli et al (2018), who found low internal consistencies of the PRFQ subscales in middle and upper socioeconomic status parents. In several studies that found low internal consistencies, removing PRFQ items with low factor loadings from subscale construction improves subscale internal consistency (e.g., Pazzagli et al, 2018; Wendelboe et al, 2021; Yule, 2021). Thus, our first aim was to examine the factor structure of the PRFQ among a low-income, racially diverse sample of maltreating and nonmaltreating mothers of preschoolers.…”
Section: Parental Reflective Functioning and Child Maltreatmentmentioning
confidence: 99%
“…In contrast, internal consistencies tend to be higher in studies that administered the PRFQ to samples in which parents were primarily college educated, partnered, and not recruited based on being at-risk (e.g., Carlone & Milan, 2021; Moreira & Fonseca, 2022; Nijssens et al, 2020)—though see Pazzagli et al (2018), who found low internal consistencies of the PRFQ subscales in middle and upper socioeconomic status parents. In several studies that found low internal consistencies, removing PRFQ items with low factor loadings from subscale construction improves subscale internal consistency (e.g., Pazzagli et al, 2018; Wendelboe et al, 2021; Yule, 2021). Thus, our first aim was to examine the factor structure of the PRFQ among a low-income, racially diverse sample of maltreating and nonmaltreating mothers of preschoolers.…”
Section: Parental Reflective Functioning and Child Maltreatmentmentioning
confidence: 99%
“…Low scores on factor 3 are considered optimal. Validation studies of the PRFQ provide evidence for its reliability and validity [ 45 , 46 ]. The version used in this study was translated by Mette Skovgaard Væver and Johanne Smith-Nielsen, Center for Early Intervention and Family Studies, University of Copenhagen.…”
Section: Methodsmentioning
confidence: 99%
“…Parental reflective functioning will be measured using the Parental reflective functioning questionnaire (PRFQ; [14]), a self-report measure of the parental ability to reflect upon the mental states of oneself and the child. In this study, we use the 15-item version of the PRFQ, which has been validated in a sample of Danish mothers of infants [55]. The items are rated on a 7-point Likert type scale going from "Completely disagree" (= 1) to "Completely agree" (= 7).…”
Section: Secondary Study Outcomesmentioning
confidence: 99%